Determinan Loyalitas Reseller Kain Tenun Ikat Troso di Grup Facebook Lapak Tenun Troso Online - Naja, Eri Safaun; Karsono, Lorena Dara Putri (Institut Agama Islam Negeri Kudus, 2026)
This research explores the factors that shape the loyalty of resellers of Troso Ikat Woven fabric resellers in the Facebook Group Lapak Tenun Troso Online. The focus is on the influence of service quality, product trust, and consumer satisfaction on reseller loyalty amidst high digital competition and the tendency to switch to other suppliers. The correlation method was applied to understand the relationship between variables through a sample of 100 respondents from a population of 3,492 members. The findings show that service quality has not sufficiently influenced loyalty due to variations in experience and service inconsistency. On the other hand, product trust has a strong positive influence, driven by product suitability, seller reliability, and minimal risk of loss. Consumer satisfaction also strengthens loyalty through positive experiences, social engagement, and supply dependence which keeps resellers making repeat transactions. These results confirm the strategy of strengthening trust and satisfaction as the key to maintaining loyalty while supporting the sustainability of local woven fabric businesses.Keywords: Service Quality, Product Trust, Consumer Satisfaction, Troso Ikat Weaving Penelitian ini mengeksplorasi faktor-faktor yang membentuk loyalitas reseller kain Tenun Ikat Troso di Grup Facebook Lapak Tenun Troso Online. Fokus tertuju pada pengaruh kualitas layanan, kepercayaan produk, dan kepuasan konsumen terhadap kesetiaan reseller di tengah persaingan digital yang tinggi dan kecenderungan berpindah ke pemasok lain. Metode korelasi diterapkan untuk memahami hubungan antarvariabel melalui sampel 100 responden dari populasi 3.492 anggota. Temuan menunjukkan kualitas layanan belum cukup memengaruhi loyalitas karena variasi pengalaman dan ketidakkonsistenan layanan. Sebaliknya, kepercayaan produk menimbulkan pengaruh positif yang kuat, didorong kesesuaian produk, keandalan penjual, dan minim risiko kerugian. Kepuasan konsumen turut memperkuat loyalitas melalui pengalaman positif, keterikatan sosial, dan ketergantungan pasokan yang membuat reseller tetap bertransaksi secara berulang. Hasil ini menegaskan strategi penguatan kepercayaan dan kepuasan sebagai kunci mempertahankan loyalitas sekaligus mendukung keberlanjutan bisnis kain tenun lokal.Kata Kunci : Kualitas Layanan, Kepercayaan Produk, Kepuasan Konsumen, Tenun Ikat Troso